การพัฒนาชีวภัณฑ์ไตรโคเดอร์มาชนิดเม็ดเพื่อการควบคุมโรคเหี่ยวเหลืองของมะเขือเทศ - กาวิชา ประภาษ; นาติโน วนารัตน์; พัฒนาสันต์ วิไลวรรณ; แสงดี อภิเดช (Thai Journal of Science and Technology, 2021)
This research aimed to develop a Trichoderma-based granular bioproduct to extend the product’s shelf life and control Fusarium oxysoprum f.sp. lycopersici (Fol). Factorial in CRD was used for experimental design. There were three factors, including encapsulated granule formulations, storage temperature, and storage time. Each formulation contained conidia of Trichoderma sp. and sodium alginate, but the concentration of glycerol and tapioca starch was varied. The products were stored at room temperature and 4 ºC from 1 to 9 months. The results showed that the viability of Trichoderma sp. from each formulation was significantly different. Storage temperature at 4 ºC provided higher viability than room temperature. The F1 formulation (sodium alginate 0.88 % + glycerol 1.5 %) provided the best result, the highest quantity of survived conidia, at room temperature storage. The amount of survived conidia was stable for 5 months of storage. F3 (sodium alginate 0.88 % + tapioca starch 1.5 %), F4 (sodium alginate 0.88 % + glycerol 1.5 % + tapioca starch 1.5 %), F5 (sodium alginate 0.88 % + glycerol 1.5 % + tapioca starch 3.7 %), and F6 (sodium alginate 0.88 %) formulations provided the highest number and stable of survived conidia at 4 ºC up to 9 months. The survived Trichoderma sp. from all formulations maintained the Fol inhibitory ability.